Theory of machines (Kinematics) - Ravi, V
The subject theory of machines forms the basis for understanding the working principles of a machine. The theoretical principles involved in machines have immediate application to practical problems. Designed as a text for the undergraduate students of mechanical engineering, it covers all the basics of mechanism and machine theory in a simple and logical manner. The basic theory presented in the book has been evolved out of simple and readily understood principles. The text begins with the discussion on various types of mechanisms and their working principles. Further it discusses the working of Oldham?s coupling, automobiles steering gears, engine pressure indicators, and estimation of velocity and acceleration using relative velocity method, complex algebra method and instantaneous centre method. Types of friction and power transmission by belt drives are also explained in detail. Finally it concludes with cam and follower mechanism